Peripheral quantitative computed tomography (pQCT) reveals low bone mineral density in adolescents with motor difficulties - Hands, B.; Chivers, P.; McIntyre, F.; Bervenotti, F.; Blee, Tanya; Beeson, B.; Bettenay, F.; Siafarikas, A. (Springer, 2015)
© 2015, International Osteoporosis Foundation and National Osteoporosis Foundation. Summary: This is the first reported study to describe local bone mineral density, assess parameters of fracture risk and report history of fractures in adolescents with motor difficulties. Motor difficulties evidenced by poor coordination in adolescence should be considered a new risk factor for below-average bone strength and structure and fracture risk. Introduction: Adolescents with motor difficulties are characterised by poor coordination and low levels of physical activity and fitness. It is possible these deficits translate into below-average bone strength and structure. The objectives of this study were to describe local bone mineral density (BMD), assess parameters of fracture risk (stress–strain index, SSI) and report history of fractures in this group. Methods: Thirty-three adolescents (13 females), mean age of 14.3 (SD = 1.5) years, with motor difficulties underwent peripheral quantitative computed tomography (pQCT) measurements at proximal (66 %) and distal (4 %) sites of the non-dominant radius (R4 and R66) and tibia (T4 and T66). One sample t test was used to compare Z-scores for total BMD, trabecular density, cortical density and stress strain index (SSI) against standardized norms. Results: Significant differences were present at R4 total density mean Z-score = -0.85 (SD = 0.7, p < 0.001), R66 cortical density mean Z-score = -0.74 (SD = 1.97, p = 0.038), R66 SSI mean Z-score = -1.00 (SD = 1.08, p < 0.001) and T66 SSI mean Z-score = -0.70 (SD = 1.15, p < 0.001). There was a higher incidence of fractures (26.9 %) compared to the normal population (3–9 %). Conclusions: Motor difficulties in adolescence should be considered a risk factor for below-average bone strength and structure and fracture risk. Strategies are needed to improve bone health in this high-risk-group.